ANALYSIS OF IMPLEMENTATION OF NON-SMOKING REGIONAL POLICIES IN A TASK FORCE ENVIRONMENT - Andi Yusuf Katili; I Kadek Satria Arsana Arsana; Ellys Rachman; Lisda Van Gobel (International Interdisciplinary Conference on Sustainable Development Goals, 2021)
That cigarette kills you is a warning listed on every circulating cigarette wrapping label, but for smokers it is only considered a meaningless slogan. This research aims to analyze the extent to which the application of non-smoking areas is effective and adhered to by employees, especially the Local Government Task Force (SKPD) of Gorontalo Province. The research method used is descriptive with a qualitative approach. The data source is obtained from primary and secondary data. The results showed that the implementation of the policy of non-smoking regional programs in the SKPD environment has not been effective due to the behavior of non-compliance of employees who are not fully aware of cigarettes can cause disease, less understanding about cigarette smoke is more harmful to passive smokers. Concluded that the Implementation of Non-Smoking Area Policy in SKPD Environment has not been fully adhered to by employees where there are still smoking not in the place that has been provided, the employees have not realized that cigarettes and their content can cause disease, and that the employees do not understand that cigarette smoke can interfere with the health of themselves and people (passive smokers) in the vicinity. Therefore, it is recommended that the Local Government be more keen to socialize so that employees comply with the regulations; aware of the dangers of cigarettes indirectly damaging to health; understand that cigarette smoke is very dangerous for himself and those around him. Keywords: Implementation, Policy, Program, Non-Smoking Area